Penerapan Manajemen dan Penatalayanan Gereja pada Gereja Pantekosta di Indonesia (GpdI) Eben Haezer Kotaraja - Rante, Yohanis; Ratang, Westim (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
The implementation of this activity carries the theme Implementation of Church Management and Stewardship at the Gpdi Eben Haezer Kotaraja Church. The method of implementing activities is done through lectures. The solution in solving problems in improving services to the Eben Haezer Kotaraja GPdI congregation is to hold Church Management and Stewardship training at Eben Haezer Kotaraja Congregation. The result of this training will be a guidebook or handbook for church services starting from the Assembly, pulpit service, Pentecostal Men's Ministry (Pelrip), Pentecostal Women's Ministry (Pelwap), Pentecostal Children's Ministry (Pelnap), Pentecostal Youth Ministry (Pelrap), Sector A and Sector B leaders, Altar Servers, Church Diakonia Section, and Church Treasurer. The output target of the community service activity is a guidebook for the Management and Stewardship of the Pentecostal Church in Indonesia (GPdI) Eben Haezer Kotaraja Congregation.